Brain Network Alterations in Alzheimer's Disease Identified by Early-Phase PIB-PET. (8th January 2018) - Fu, Liping; Liu, Linwen; Zhang, Jinming; Xu, Baixuan; Fan, Yong; Tian, Jiahe
Abstract : The aim of this study was to identify the brain networks from early-phase 11 C-PIB (perfusion PIB, pPIB) data and to compare the brain networks of patients with differentiating Alzheimer's disease (AD) with cognitively normal subjects (CN) and of mild cognitively impaired patients (MCI) with CN. Forty participants (14 CN, 12 MCI, and 14 AD) underwent 11 C-PIB and 18 F-FDG PET/CT scans. Parallel independent component analysis (pICA) was used to identify correlated brain networks from the 11 C-pPIB and 18 F-FDG data, and a two-sample t -test was used to evaluate group differences in the corrected brain networks between AD and CN, and between MCI and CN. Our study identified a brain network of perfusion (early-phase 11 C-PIB) that highly correlated with a glucose metabolism ( 18 F-FDG) brain network and colocalized with the default mode network (DMN) in an AD-specific neurodegenerative cohort. Particularly, decreased 18 F-FDG uptake correlated with a decreased regional cerebral blood flow in the frontal, parietal, and temporal regions of the DMN. The group comparisons revealed similar spatial patterns of the brain networks derived from the 11 C-pPIB and 18 F-FDG data. Our findings indicate that 11 C-pPIB derived from the early-phase 11 C-PIB could provide complementary information for 18 F-FDG examination in AD.